Последние свидетели: (сто недетских колыбельных) / С. Алексеевич - Алексиевич Светлана (Пальмира, 2004)
Экземпляры: АБ (20221208) / Инвентарный номер: 42185 / Цена: 99.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 48 / ББК: 84(2Рос=Рус)6